2001
DOI: 10.2176/nmc.41.325
|View full text |Cite
|
Sign up to set email alerts
|

Two-Staged Operation for Thoracolumbar Osteomyelitis Following Methicillin-Resistant Staphylococcus Aureus Infection of a Craniectomy Wound. Case Report.

Abstract: A previously healthy 53-year-old woman developed pyogenic vertebral osteomyelitis (PVO) manifesting as progressive lumbago following wound infection of a decompressive craniectomy performed for brain contusion caused by a traffic accident. Magnetic resonance imaging disclosed vertebral osteomyelitis at T-12 and L-1 with paravertebral abscess. Anterior debridement and fusion using autografts were performed at the first operation. Methicillin-resistant Staphylococcus aureus (MRSA) was cultured from the abscess s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…A method that is in contrast to ours was presented in the literature by Yamada et al, 14 who reported successful clinical experience with methicillin-resistant S. aureus spondylitis by a two-stage operation. They performed anterior debridement at the first stage, and then applied posterior instrumentation after giving postoperative chemotherapy for 4 weeks and confirming that the infection had been suppressed.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A method that is in contrast to ours was presented in the literature by Yamada et al, 14 who reported successful clinical experience with methicillin-resistant S. aureus spondylitis by a two-stage operation. They performed anterior debridement at the first stage, and then applied posterior instrumentation after giving postoperative chemotherapy for 4 weeks and confirming that the infection had been suppressed.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, for those whose infections are resistant to antibiotic chemotherapy and who have major bone destruction, neurologic impairment, recurrence of infection, and severe pain, surgical treatment by anterior debridement and bone grafting is indicated. [1][2][3]8,9,13 Generally, debridement of the infected site and autogenous bone graft are the surgical procedures of first choice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Quando se realiza primeiro a cirurgia por VA para desbridamento e enxerto o paciente é submetido a um maior tempo cirúrgico e maior perda de sangue, apesar de terem sido descritos bons resultados com essa estratégia 11,15,16 . Nas situações em que a primeira cirurgia é a VP, menos agressiva e com tempo cirúrgico menor, obtém-se estabilização e redução importante da intensidade das dores, promovendo diminuição e algumas vezes até resolução da infecção anterior.…”
Section: Discussionunclassified